Game performance basics mastering training for beginners - Lutkova, N. V.; Makarov, Y. M.; Ramzaytseva, A. A.; .Mokina, E. I.; Zaitsev, A. A. (Theory and Practice of Physical Culture, 2019)
Objective of the study was to develop a game basics (guiding framework) mastering training algorithm for beginners to help them acquire the primary technical/ tactical skills for success in the long-term training process. The study was designed as a part of a three-year practical trainers` training program in team sports, with a special emphasis on the situation-specific response trainings.